2013
DOI: 10.1038/hr.2013.134
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the association between serum uric acid levels and cardiac hypertrophy in patients with chronic kidney disease

Abstract: Several studies have documented an association between serum uric acid (SUA) concentration and cardiac hypertrophy in hypertensive patients; however, the association remains unclear in chronic kidney disease (CKD) patients. If there is an association between SUA and hypertrophy in these patients, it is unknown whether the association is different between men and women. Our aim in this study is to determine whether SUA is associated with cardiac hypertrophy in CKD patients, focusing on any sex differences. Two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
43
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 46 publications
3
43
0
1
Order By: Relevance
“…In addition, the strength of the association between SUA and certain cardiac abnormalities might differ between women and men. 3,[20][21][22] We found that among patients with sinus rhythm, SUA was independently associated with diastolic dysfunction only in women. 21) In a previous study, by analyzing the data from male patients, we showed that SUA is associated with cardiac hypertrophy.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, the strength of the association between SUA and certain cardiac abnormalities might differ between women and men. 3,[20][21][22] We found that among patients with sinus rhythm, SUA was independently associated with diastolic dysfunction only in women. 21) In a previous study, by analyzing the data from male patients, we showed that SUA is associated with cardiac hypertrophy.…”
mentioning
confidence: 69%
“…2,3) On the other hand, however, whether uric acid per se plays a causal role in cardiovascular morbidity remains a subject of debate, irrespective of various epidemiological and Mendelian randomization studies. [4][5][6][7][8][9][10][11] Editorial p. 467 To assess whether serum SUA is associated with cardiac hypertrophy and heart failure, 12) we may have to take various possible confounders into account, such as estimated glomerular filtration rate (eGFR), phosphate, 13) and the recently identified phosphaturic hormone fibroblast growth factor 23 (FGF23) that might directly induce hypertrophy of cardiomyocytes.…”
mentioning
confidence: 99%
“…The rate of hyperuricemia increased and the mean eGFR decreased with increased age in both men and women, especially in older women. These gender difference was observed in other studies as well and was suggested to relate to natural aging, the decline in female hormone levels in older women and the reduced excretion of uric acid from the kidney (Chang et al, 2010;Krishnan, Bennett, & Chen, 2014;Liu et al, 2014;Lu et al, 2014;Yoshitomi et al, 2014).…”
Section: Normo-albuminuriamentioning
confidence: 71%
“…However, researches focusing on the relation between cardiovascular complications and hyperuricemia in CKD patients are rare. Ryota Yoshitomi [20] found a significant correlation between hyperuricemia and ventricular hypertrophy in women, but there was no significant correlation in men. Researches focusing on cardiovascular complications in early-stage CKD are even scarcer.…”
Section: Discussionmentioning
confidence: 99%